2011
DOI: 10.1007/s00109-011-0737-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability

Abstract: Sunitinib, a novel oral multi-targeted tyrosine kinase inhibitor for patients with metastatic renal cell carcinoma (mRCC) and advanced gastrointestinal stromal tumor, has a good prospect for clinical application and is being investigated for the potential therapy of other tumors. We observed the phenomenon that drinking tea interfered with symptom control in an mRCC patient treated with sunitinib and speculated that green tea or its components might interact with sunitinib. This study was performed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 27 publications
4
50
0
1
Order By: Relevance
“…Several reports have indicated pharmacokinetic interaction between sunitinib and drugs (Di Gion et al, 2011) or foods Ge et al, 2011;van Erp et al, 2011). In particular, a clinical study demonstrated that coadministration of rifampicin, an inducer of CYP3A4, significantly decreased systemic exposure to sunitinib (Di Gion et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated pharmacokinetic interaction between sunitinib and drugs (Di Gion et al, 2011) or foods Ge et al, 2011;van Erp et al, 2011). In particular, a clinical study demonstrated that coadministration of rifampicin, an inducer of CYP3A4, significantly decreased systemic exposure to sunitinib (Di Gion et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced bioavailability of the anticancer drug sunitinib has been recently related to co-administration with EGCG. 28 These observations show the need to conduct further studies to ascertain the interaction between EGCG and different anticancer drugs, for each particular type and stage of cancer. The possibility of antagonistic interactions must be taken into account in the development of new cancer therapy strategies based on drug-EGCG cotreatments.…”
Section: Limitations To the Use Of Egcg As Chemosensitizer For Anticamentioning
confidence: 99%
“…27,28 [ Increase; Y decrease; [Y modulation; AMPK, AMP-activated protein kinase; AR, androgen receptor; ATO, arsenic trioxide; BCRP, breast cancer resistant protein; CBR1, carbonyl reductase 1; DPD, dihydropyrimidine dehydrogenase; ER, estrogen receptor; GRP78, glucose-regulated protein 78; MDR1, multidrug resistance protein; P-gP, Pglycoprotein; ROS, reactive oxygen species; TSA, trichostatin-A.…”
mentioning
confidence: 99%
“…The values of C max and AUC of CYP3A and P-gp substrates, diltiazem, verapamil, tamoxifen, simvastatin, and nicardipine were increased after rats were exposed to EGCG, suggesting that EGCG might inhibit CYP3A and/or P-gp activities [28-30, 33, 35]. However, the C max and AUC of other CYP3A4 substrates (e.g., quetiapine, sunitinib) were reduced in rats administered GTE or EGCG [27,36]. GTE decreased the C max and AUC of clozapine in rats, ostensibly due to the metabolic induction of CYP1A2 [32].…”
Section: Interaction Assessments Using Animal Modelsmentioning
confidence: 99%